7z-9=9z+19

Simple and best practice solution for 7z-9=9z+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7z-9=9z+19 equation:


Simplifying
7z + -9 = 9z + 19

Reorder the terms:
-9 + 7z = 9z + 19

Reorder the terms:
-9 + 7z = 19 + 9z

Solving
-9 + 7z = 19 + 9z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-9z' to each side of the equation.
-9 + 7z + -9z = 19 + 9z + -9z

Combine like terms: 7z + -9z = -2z
-9 + -2z = 19 + 9z + -9z

Combine like terms: 9z + -9z = 0
-9 + -2z = 19 + 0
-9 + -2z = 19

Add '9' to each side of the equation.
-9 + 9 + -2z = 19 + 9

Combine like terms: -9 + 9 = 0
0 + -2z = 19 + 9
-2z = 19 + 9

Combine like terms: 19 + 9 = 28
-2z = 28

Divide each side by '-2'.
z = -14

Simplifying
z = -14

See similar equations:

| 23z=76 | | 9+t=15 | | 81x-3969=4 | | [x-3+2x-15]=9 | | 18-3p=-2+2p | | 6(3s+3)=162 | | 3(x-1)=5-(x-3) | | 9-6x-6-9x=6 | | Z/7-9=10 | | 64x+184=0 | | 15/65=x/5 | | 7g+18=9g | | f(x)=dx^2+ex+f | | p+32.1=47.8 | | 4(3x+1)=25 | | 6(c+3)=3+5c | | 99+9x=0 | | 2(y-5)+40=20 | | -8+2x=-x+4 | | 2z*9+6=-3 | | -6(n-2)-(2n-3)=-9n | | 0=2c+10 | | 2(2l+5)=34 | | U+7=13 | | 3s+t=19.25 | | 9-y=-15 | | n-(-12)=-5 | | 4x-(2x+4)=x-2 | | x^4-7x^3-49x^2+343x=0 | | 5x+3x=7x+3 | | m=-1 | | 48=13/7x+9 |

Equations solver categories